Gerakan Sosial Korban LUSI (Lumpur Sidoarjo) - Ricka Octaviani; Reza Shintia Eka; Dwi Alfin K (Universitas Muhammadiyah Sidoarjo, 2015)
This study aimed to describe the forms of social movements Sidoarjo mud victim (LUSI) and to describe the factors supporting and inhibiting of the formation of social movements Sidoarjo mud victim (LUSI). The method in this research used descriptive qualitative research. Based on the research, showed that social movements Sidoarjo mud victim was a movement that is arising from a sense of common destiny that wants to fight for compensation due Lapindo mud disaster. Some forms of social movements such as KLM (mud victims sue), GKLL (movement Lapindo mud victims), PPKL (community care of mud victims) and social movements is initiated by the leader of the neighborhood. Some of the supporting factors to form of social movements victims included tighten the relationship of victims; movement to reach agreement on compensation; as supervisor of payment of compensation; as well as a movement justice for the victims. While the factors inhibiting included Sidoarjo Mud Management Agency hard to be found; the leadership of the government was not facilitating the communication between the victim and the Sidoarjo Mud Management Agency; demonstrations or meeting with leaders so difficult; as well as different perception among NGO's with the social movements.